2012
DOI: 10.1161/cir.0b013e31826e1058
|View full text |Cite
|
Sign up to set email alerts
|

Third Universal Definition of Myocardial Infarction

Abstract: Criteria for acute myocardial infarction The term acute myocardial infarction (MI) should be used when there is evidence of myocardial necrosis in a clinical setting consistent with acute myocardial ischemia. Under these conditions any one of the following criteria meets the diagnosis for MI: ● Detection of a rise and/or fall of cardiac biomarker values [preferably cardiac troponin (cTn)] with at least one value above the 99th percentile upper reference limit (URL) and with at least one of the following: y Sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
1,152
2
36

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,802 publications
(1,199 citation statements)
references
References 109 publications
9
1,152
2
36
Order By: Relevance
“…In 234 territories from 234 patients, 63 patients (26.9%) showed a post‐PCI cardiac troponin I (cTnI) level >5 times the upper reference limit (≥1.0 ng/mL) based on blood samples taken at an average of 20.1±2.4 hours after PCI. The institutional 99th percentile upper reference limit for diagnosing acute coronary syndrome is 0.20 ng/mL, and PCI‐related myocardial injury was defined as a cTnI level >1.0 ng/mL (0.20 ng/mL; institutional upper reference limit ×5) based on the third universal definition of myocardial infraction 22. In these 63 patients, 4 had distal embolization exhibiting a transient slow flow or no reflow at the time of PCI with ECG changes, and 10 showed side‐branch occlusion (>1.5 mm in diameter) during PCI with wall motion abnormality detected by ultrasound examination after PCI and/or ECG changes.…”
Section: Resultsmentioning
confidence: 99%
“…In 234 territories from 234 patients, 63 patients (26.9%) showed a post‐PCI cardiac troponin I (cTnI) level >5 times the upper reference limit (≥1.0 ng/mL) based on blood samples taken at an average of 20.1±2.4 hours after PCI. The institutional 99th percentile upper reference limit for diagnosing acute coronary syndrome is 0.20 ng/mL, and PCI‐related myocardial injury was defined as a cTnI level >1.0 ng/mL (0.20 ng/mL; institutional upper reference limit ×5) based on the third universal definition of myocardial infraction 22. In these 63 patients, 4 had distal embolization exhibiting a transient slow flow or no reflow at the time of PCI with ECG changes, and 10 showed side‐branch occlusion (>1.5 mm in diameter) during PCI with wall motion abnormality detected by ultrasound examination after PCI and/or ECG changes.…”
Section: Resultsmentioning
confidence: 99%
“…A recent randomized, double‐blind, crossover intervention study of healthy adults from Shanghai, China, for example, reported that substantial reductions in PM 2.5 exposures for 48 hours from air purification resulted in cardiopulmonary benefits, including decreases in several circulating inflammatory and thrombogenic biomarkers and lower systolic and diastolic blood pressure 27. Given these implied adverse mechanisms, in the context of universal definition and clinical classification of MI,28 these results suggest that there are differential effects of PM 2.5 exposures on different types of MI. It is likely, for example, that MI events that occur in those with no CAD by angiogram would be classified as type 2 MI, and these events would be less likely to be associated with short‐term elevated exposure to PM 2.5 air pollution than type 1 (or even possibly type 3) MI events.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing an accurate diagnosis of NSTEMI in dialysis patients can be problematic because troponin increases and nonspecific electrocardiographic abnormalities are common and typical symptoms of acute coronary syndrome are less frequent,5 but prevalence of obstructive coronary artery disease is high. Consequently, differentiating type 1 (or spontaneous) AMI from type 2 AMI (caused by supply/demand mismatch), particularly in the context of chronic baseline troponin elevation, can be difficult 18. These diagnostic challenges, compounded by the transition of the preferred biomarker from creatinine kinase to higher sensitivity troponin assays, could potentially contribute to the remarkable uptick in diagnostic codes for NSTEMI between 1993 and 2008.…”
Section: Discussionmentioning
confidence: 99%